The Outcome of Ethanol Directed Sclerotherapy for the Management of Endometrioma: A Systematic Review - Kamajaya, I Gusti Ngurah Agung Trisnu; Suardika, Anom; Mahayasa, Putu Doster; Budiana, Nyoman Gede; Abhimantra, Gede Bagus Kantwa (Indonesian Journal of Perinatology, 2024)
Background and Objectives: Ovarian endometriomas, commonly known as chocolate cysts, are prevalent gynecological conditions associated with chronic pelvic pain and infertility. Current standard treatment, laparoscopic cystectomy, poses risks such as reduced ovarian reserve. Ethanol-directed sclerotherapy has emerged as a minimally invasive alternative aiming to preserve ovarian tissue while treating endometriomas. This systematic review evaluates the outcome of ethanol directed sclerotherapy for the management of endometrioma. Methods: Following PRISMA guidelines, databases including PubMed, EMBASE, and Cochrane were searched in January 2024 using “endometrioma and sclerotherapy.” Inclusion criteria encompassed studies reporting success rate (SR), RR, and pregnancy rate (PR) post-treatment. Nine studies involving 499 patients were analyzed. Results: Ethanol sclerotherapy demonstrated >80% SR in six studies and <30% RR in seven studies, indicating efficacy in reducing recurrence. However, its impact on ovarian reserve remains inconclusive. Pregnancy outcomes were inconsistently reported, with one study achieving 100% PR, while others ranged from 0% to >30%. Variability in techniques, such as ethanol concentration and retention time, likely influenced outcomes. Conclusions: Ethanol sclerotherapy offers a promising alternative to surgery, showing lower RR and potential preservation of ovarian function. Despite these benefits, inconsistencies in procedural protocols and limited data on long-term fertility outcomes necessitate further research. Standardized guidelines and larger cohort studies are essential to establish sclerotherapy's role in endometrioma management, especially for fertility preservation.